Simulators As Visual Aids To Reinforce Courses In Automation And Industrial Robotics - Sánchez-Chero, Manuel; Sánchez-Chero, Jose Antonio; Ortega Cabrejos, Mónica Ysabel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The basic automation courses present in various engineering careers, have seen the need to implement new methodologies that bring students closer to real practice. During the pandemic, the need to implement teaching methodologies such as simulation based on visual aids to achieve this objective was observed. That is why this literature review aims to generate a scope on the use of simulators in automation courses, and to present the simulators that have been successfully used in the teaching of this course, in addition to highlighting the advantages of its use in education.